On fragile waves - Yu, E. Lily (Erewhon Books, 2021)
"The haunting story of a family of dreamers and tale-tellers looking for home in an unwelcoming world. Traces one girl's migration from war to peace, loss to loss, home to home. Firuzeh and her brother Nour are children of fire, born in an Afghanistan fractured by war. When their parents, their Atay and Abay, decide to leave, they spin fairy tales of their destination, the mythical land and opportunities of Australia. As the family journeys from Pakistan to Indonesia to Nauru, heading toward a hope of home, they must rely on fragile and temporary shelters, strangers both mercenary and kind, and friends who vanish as quickly as they're found. When they arrive in Australia, what seemed like a stable shore gives way to treacherous currents."--Publisher description.